Monitoring of Multi Purpose Rack (MPR) interlocking system of Railway Stations based on Internet of Things - Yuannisa, Ilfa; Hambali (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Signaling devices such as signal lights and point machines are very important in railway signaling interlocking systems, where voltage and current affect their performance. Fluctuations in these parameters can cause malfunctions and endanger safety. Current manual monitoring is considered inefficient, error-prone, and slow to respond to problems. For this reason, an automatic monitoring system based on the Internet of Things (IoT) is needed to monitor parameters in real-time. The prototype uses two ESP32 microcontroller modules as data senders and receivers. Data is displayed via a TFT LCD screen and the Blynk application. The system is also equipped with a buzzer alarm to detect abnormal conditions. The test results show that the prototype monitoring device that was made can work well and in accordance with the design, where the PZEM-004T sensor is able to read current and voltage accurately and the buzzer alarm is able to detect when an abnormal condition occurs in the signaling device